Chronic hepatitis E virus-induced spinal cord atrophy in a patient with chronic lymphatic leukemia: a case report and interdisciplinary management proposal - Ritter, Marvin; Yomade, Olaposi; Holtz, Ben-Ole; Deinhardt-Emmer, Stefanie; McLean, Aaron Lawson; Hartinger, Stefanie; Bechwar, Julia; Schwab, Matthias; Huss, André; Mawrin, Christian; Axer, Hubertus; Schrenk, Karin G.; et al. (Frontiers in Immunology, 2024)
Abstract Background: The hepatitis E virus (HEV) can cause acute viral hepatitis with or without neurological manifestations, and occasionally progresses to chronic infection in immunocompromised individuals. The management of chronic HEV infection in cancer patients may be challenging due to the complex immunological constellation. Furthermore, the diagnostic workflow and the impact on quality of life of neurological HEV manifestations in immunocompromised patients have not been sufficiently delineated previously. Case Description: A 61-year-old male with systemically treated chronic lymphocytic leukemia (CLL) experienced a slowly progressive atrophy of the spinal cord due to a chronic HEV infection. Despite continuous antiviral treatment with ribavirin, the patient's neurological condition continued to deteriorate, particularly following subsequent attempts to treat CLL. Treatment with obinutuzumab resulted in acute bowel and urinary retention and a further deterioration of motor skills, prompting the discontinuation of obinutuzumab. The patient's neurological status improved after the administration of intravenous immunoglobulins. Conclusion: This case study provides a comprehensive long-term follow-up of a cancer patient with chronic HEV infection and associated CNS involvement, which resulted in progressive neurological disability over several years. The challenges faced in diagnosing new neurological symptoms in patients undergoing immunosuppressive cancer treatment underscore the need for an interdisciplinary diagnostic approach that includes HEV testing. We propose a diagnostic pathway for future validation in immunocompromised cohorts presenting with neurological symptoms, emphasizing its potential to enhance clinical outcomes.